Turbulensi Geopolitik dan Nexus Diplomasi Lingkungan Indonesia - Yunita Asmawati (Andalas Journal of International Studies (AJIS), 2025)
This article narrates the condition of global geopolitical turbulence stemming from a foreign policy event between the United States and China following President Donald Trump's tariff policy, which has created a new map in systemic relations. Whether it is in foreign policy interactions or the patterns of state alliances beyond the contestation of global power. This momentum coercively tests the strength of world nations, including Indonesia, in responding to global uncertainty. At the same time, this geopolitical turbulence creates a vacuum in leadership profiles on the global stage that provide solutions to the environmental crisis and also presents an imbalance in the availability of the Supply Chain with the energy transition. Indonesia actually has a structure within domestic entities that should strengthen the nexus of Indonesia's environmental diplomacy in facing that turbulent period. Especially by taking lessons from ancient Chinese history. This article finds that a state's strength amidst geopolitical turbulence to endure and increase its bargaining power does not always stem from material factors, but from perceptions that shape the state's identity. Therefore, this article is conceived using an interpretative qualitative design. Specifically, by using the thoughts of Katzenstein (holistically) and Wendt (systemically) in layers, without mixing the ontology of both within the realm of constructivist international relations thought. The theoretical and practical implication is that when environmental diplomacy and geopolitics are able to mutually reinforce and positively shape each other.